Influence of potassium nutrition and the nitrate ammonium ratio on the putrescine and spermidine contents in banana vitroplants - Zaidan, H. A.; Broetto, F.; de Oliveira, E. T.; Gallo, L. A.; Crocomo, O. J. (Marcel Dekker Inc, 1999)
Potassium (K) is required in high doses by the banana (Musa sp.) plant and interacts with other nutrient elements in which banana tissues are maintained under in vitro condition as a consequence modifications in the plant metabolism take place mainly in nitrogen (N) compounds, such as proteins, amino acids, and secondary compounds. When K is present in concentrations lower than that required, diamines such as putrescine and poliamines are formed. This metabolic disorder can also be correlated with the presence of different inorganic N forms, such as nitrate (NO3) and ammonium (NH4), and the ratios between both ions as well. In order to follow the physiological performance of the interrelationships, K/putrescine and of the NO3/NH4 ratio in the tissue of banana vitroplantlets, shoot apex of two banana cvs. Nanica and Prata Ana were maintained in modified MS medium in the presence of six different doses of K: 5, 10, 15, 20, 25, and 30 mM. After the period of tissue proliferation the cultures were transferred to rooting media containing the same different K doses. Dry matter, K, putrescine, and spermidine contents and their accumulation were determined in the shoots and roots of the vitroplantlets and in the shoot apex of the explant donor cultivar as well as the corresponding values for the whole vitroplantlets calculated. The data were statistically analyzed. The contents and accumulations of putrescine and spermidine in banana tissues were enhanced as K concentration decreased in the medium: four times (0.19% of the dry matter) for cv. Nanica and eight times (0.25% of the dry matter) for cv. Prata Ana. This behavior was not only related to the K depletion but to the NO3/NH4 ratio as well.